1999
DOI: 10.1002/(sici)1097-0290(19990820)64:4<401::aid-bit3>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of ammonium into intracellular UDP‐activated N‐acetylhexosamines and into carbohydrate structures in glycoproteins

Abstract: The negative effects of ammonia on animal cells, especially in vitro cultures, are well known, but the mechanism of how ammonia inhibits cell growth and influences the glycosylation of proteins is not completely understood. We investigated the ammonium action on the synthesis of the intracellular UDP-N-acetylhexos- amines (UDPGNAc), which are precursors of glycosylation as well as on N-linked oligosaccharides of a recombinant human IL-2 mutant variant model glycoprotein expressed in BHK-21 cells under defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…These effects depend on several cellular factors: (1) enzyme repertoire and localization (Ferrara et al, 2006;Meynial-Salles and Combes, 1996); (2) competition between different enzymes for one substrate (Umaña and Bailey, 1997); (3) transit time of the glycoproteins through the Golgi apparatus (Hooker et al, 1999;Nabi and Dennis, 1998); (4) levels of nucleotide sugar donors (Nyberg et al, 1999;Valley et al, 1999); and last but not the least (5) competition between different glycosylation sites on the protein for the same pool of enzymes (Schachter et al, 1983).…”
Section: Heterogeneity In N-glycosylation Pathwaymentioning
confidence: 99%
See 3 more Smart Citations
“…These effects depend on several cellular factors: (1) enzyme repertoire and localization (Ferrara et al, 2006;Meynial-Salles and Combes, 1996); (2) competition between different enzymes for one substrate (Umaña and Bailey, 1997); (3) transit time of the glycoproteins through the Golgi apparatus (Hooker et al, 1999;Nabi and Dennis, 1998); (4) levels of nucleotide sugar donors (Nyberg et al, 1999;Valley et al, 1999); and last but not the least (5) competition between different glycosylation sites on the protein for the same pool of enzymes (Schachter et al, 1983).…”
Section: Heterogeneity In N-glycosylation Pathwaymentioning
confidence: 99%
“…Culture conditions such as accumulation of ammonia, dissolved oxygen level, nutrient contents, pH level and temperature, may have great effects on the distribution of glycan structures (microheterogeneity and macroheterogeneity) found on the final recombinant protein products. Those factors may cause one or more mechanisms in the following: (1) the depletion of the cellular energy state (Rearick et al, 1981;Valley et al, 1999); (2) disruption of the local ER and Golgi environment, such as pH (Andersen and Goochee, 1995) or redox potential (Restelli et al, 2006); (3) alteration of glycosyltransferase activities (Chen and Harcum, 2006;Chotigeat et al, 1994); and (4) changes in the Nglycosylation precursor pool, such as nucleotides, nucleotide sugars (Kochanowski et al, 2008;Nyberg et al, 1999) and lipid precursors (Stoll and Krag, 1988). …”
Section: Culture Parameters That May Affect Glycosylationmentioning
confidence: 99%
See 2 more Smart Citations
“…A change in the U ratio has been shown to affect the N-glycan complexity of glycoproteins (Gawlitzek et al 1998). Other studies revealed that an increase in the UDPGNAc pool can be the result of ammonium uptake which accumulates in cell cultures due to cellular metabolism and thermal degradation of glutamine (Gawlitzek et al 1999;Valley et al 1999;Ryll et al 1994).…”
Section: Introductionmentioning
confidence: 99%